The virtual experience of the course Drama for English as Second Language at the Sede del Pacífico of the Universidad de Costa Rica - Salas Alvarado, Jonathan (2021)
This article systematizes the experience lived by the teacher and the students of the course Drama for English as Second Language during the first semester of 2020. This semester was particularly marked by the beginning of the COVID-19 pandemic. The article provides definitions of terms used during the course but most importantly it deals with the adaptation process the teacher went through to adjust the contents, activities, and instruction of this course to a new virtual reality that had never been experienced by any of the participants (including the teacher). An important part of the course is to approach the participants (11 English Teaching senior students) to different drama and theater techniques that can be used in the English classroom. So, the article also mentions the activities that were implemented, the way they were developed and it offers the perception of the participants about the course itself, the job done by the teaching when adapting the contents, and their criteria regarding the activities presented so that they, as future teachers, can talk about the teaching potential those activities have. The techniques were developed during the whole semester and as long as they were implemented, participants were requested to provide their opinions regarding positive and negative aspects of the activities developed, that information was kept and then systematized. Also, by the end of the semester, participants were given a digital instrument that helps them evaluate the course and offer their opinions and ideas about it. The results are very positive and encouraging since participants, despite the pandemic, mentioned being satisfied with the development of the course and see a lot of teaching potential in the activities developed during the semester.